Forensic as a tool of counteracting factoring risks - NEZHYVA Марія; MYSIUK Вікторія (Ius Modernum, 2021)
Background. In modern market conditions, the characteristics of most companies are low liquidity, working capital shortage, difficulty in obtaining credit. Under such conditions, financial flow management becomes increasingly important. One of the possible options for increasing them is factoring, which creates a basis for sustainable economic development of the business. Analysis of recent research and publications.Debatable issues need to be addressed in order to formulate a comprehensive approach to forensics in the context of factoring risk management in response to the COVID crisis. The aim of the article is to study the trends of factoring operations and to establish methods of forensics in terms of factoring risk management in response to the COVID crisis. Materials and methods. The study used general and specific methods of cognition of economic phenomena and processes to analyze the impact of the COVID-19 pandemic on business and forensic methods in the management of factoring risks in response to the COVID crisis. Results. The article considers the reasons for the use of factoring in Ukraine and highlights national measures to combat the economic consequences of the COVID-19 pandemic. The growth trends of factoring turnover and GDP in the countries of the European Union are studied. The top 5 countries in the factoring market in the EU have been identified. The risks associated with factoring operations are described. The professional directions of forensics in the conditions of risk management of factoring business are described. Conclusion. The use of forensic procedures by companies in order to minimize the risks of fraud, will significantly increase the level of risk management of companies and make optimal management decisions based on this to ensure permanent profitability of factoring operations.